MERANCANG ORGANISASI PEMBELAJARAN : LITERATURE REVIEW - Makmur Syukri; Rizky Sembiring Depari (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Abstract The learning organization is a concept in which an organization continuously improves its capacity to create the future. Designing a learning organization involves a variety of key elements, including an organizational culture that supports learning, leadership that encourages learning, an organizational structure that facilitates the exchange of information, and a reward system that rewards learning. First, an organizational culture that supports learning is characterized by a spirit of openness, a sense of security to explore, and an encouragement to continue learning. Leaders play an important role in building this culture through example and supportive policies. Second, organizational structures that facilitate learning enable smooth information flow, cross-functional collaboration, and access to knowledge resources. This can be achieved through team design, effective communication systems, and adequate technology infrastructure. Third, a reward system that appreciates learning encourages individuals to engage in self-development activities and share knowledge. Incentives can take the form of compensation, recognition, or career development opportunities. By designing these elements in an integrated manner, organizations can create an environment conducive to continuous learning and adaptation, enabling them to respond to environmental changes quickly and innovatively.